Interdisciplinary dynamic fluid physics learning in the river environment using the discovery learning model: student environmental literacy study - Santiani, Santiani; Rusmulyanti, Ayu Putri; Haryono, Agus; Winarto, Winarto; Reffiane, Fine (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This research aims to determine environmental literacy and the influence of interdisciplinary environmental dynamic fluid physics learning using the Discovery Learning model on students' environmental literacy. This research is quantitative research using a pre-experimental one-group pretest-posttest design method. The technique used in this research is the saturated sample technique, which is a data analysis technique using paired samples t-test. Learning environmentally integrated dynamic fluid physics using the Discovery Learning model can increase students' environmental literacy and have a significant effect on students' knowledge, attitudes and behaviour towards the river environment. Increasing students' ecological literacy is influenced by the implementation of learning, which is quite good, and the students are active. Environmental integration physics learning must continue to be developed so that it becomes an example for teachers to manage classes with environmental literacy outcomes and as an activity to conserve freshwater resources so that the environment is sustainable.